Phonics Instruction and Perceptions of Teachers in Ave Maria Amnatcharoen School in Thailand (NOBEL: Journal of Literature and Language Teaching, 2021)
This paper aimed to explore how teachers implemented effective techniques of teaching phonics and the teachers’ perceptions of the effects of teaching phonics to the elementary school students of Ave Maria Amnatcharoen School in Thailand. The writers employed qualitative research. Five teachers who were teaching phonics in Ave Maria Amnatcharoen School of Thailand were the research participants. The writers used a questionnaire and an interview. Findings showed that most of the teachers perceived the process of implementing effective techniques in teaching phonics positively. The participants regularly employed various techniques in teaching phonics to the students. Furthermore, the participants also had positive perceptions of the effects of implementing effective techniques in teaching phonics. Most teachers agreed that the students had developed their reading skills through learning phonics. However, there were still some students who did not improve in their reading skills through learning phonics.